Spór o istotę zła. Hannah Arendt w pismach Gustawa Herlinga-Grudzińskiego - Panas, Paweł (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The article attempts to trace Hannah Arendt’s presence in Gustaw Herling-Grudziński’s writing. The first time she appears in his texts is as the author of Eichmann in Jerusalem: A Report on the Banality of Evil – a book that the writer considered an exceptionally important voice in reflections about the nature of totalitarian systems and in the dispute over the nature of evil both in individual and metaphysical sense. Arendt’s analyses of basic dehumanisation mechanisms were close to him; he is fascinated by the soundness of Arendt’s key thesis on the ‘banality of evil.’ At the same time, Herling-Grudziński disputes with Arendt, indicating certain shortcomings in her thinking, mostly related to cognitive limitations resulting from her proposed take on the key problematics and partial disconsonance between theoretical disquisitions and existential experience. This criticism is limited and eventually Herling-Grudziński himself disputes with Arendt’s main critics. These issues are discussed in the final section of the article.